Community Empowerment Collaboration as a Basis for Community Economic Improvement through Tourism Village Icons: Kolaborasi Pemberdayaan Masyarakat sebagai Dasar Peningkatan Perekonomian Masyarakat melalui Ikon Desa Wisata - Tirtoni, Feri (Procedia of Social Sciences and Humanities, 2022)
This community service activity aims to increase the synergy between the community and the government in the development of village tourism. Interviews will be conducted so that it will be known how the community’s opinion on the condition of Penambangan Village tourism, its condition, how it is managed, and how the concept of future development will be. Food court (pujasera) is a culinary tourism destination that was just inaugurated in early 2022, and is an asset of BUMDes. Food court is one of the biggest tourist spots in Penambangan Village. Penambangan Village also has village tours that are still in the planning stage, namely river tours beside provincial roads, and outbound park in teak forest areas. From the results of this activity, it can be concluded that the tourism development of Penambangan Village is well-conceived development, starting from planning, development, and so on, and there are many potential suggestions from the community regarding Penambangan Village tourism, so it can be concluded that the cooperation between the village government with the community is urgent for the development of village tourism. The main goal of a tourist village is to improve the welfare of the community, and this goal can be achieved with good management.